2014
DOI: 10.2478/pjvs-2014-0053
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine (SSRI) treatment of canine atopic dermatitis: a randomized, double-blind, placebo-controlled, crossover trial

Abstract: This study investigated effects of a fluoxetine (selective serotonin reuptake inhibitors; SSRI, 1 mg/kg) on pruritus in canine atopic dermatitis (CAD). After 4-weeks of base-line observation, 8 dogs with CAD entered a 2-months randomized, double-blind, placebo-controlled, crossover trial comparing fluoxetine with placebo. Clinical efficacy was evaluated using a Canine Atopic Dermatitis Extent and Severity Index (CADESI-03) and Pruritus Visual Analog Scale (PVAS). Six dogs completed the study [two out of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“… An RCT showed no benefit of low level laser therapy in dogs with localized pedal AD (QOE 2) [ 56 ]. Similarly, the selective serotonin reuptake inhibitor (SSRI) fluoxetine, given at 1 mg/kg orally once daily, showed no clinical efficacy in a small RCT of dogs with AD (QOE 2) [ 57 ]. …”
Section: Introductionmentioning
confidence: 99%
“… An RCT showed no benefit of low level laser therapy in dogs with localized pedal AD (QOE 2) [ 56 ]. Similarly, the selective serotonin reuptake inhibitor (SSRI) fluoxetine, given at 1 mg/kg orally once daily, showed no clinical efficacy in a small RCT of dogs with AD (QOE 2) [ 57 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the behavioral examination, the owner reported that the patient suffered from dermatological disorders for which he was prescribed monoproteic nutrition by the attending veterinarian. In this respect, fluoxetine seems to also have some beneficial effects in relieving inflammatory itching and/or pain [ 35 , 36 ], although it is not generally prescribed to treat canine atopic itch [ 37 ]. On the other hand, given its ability to bind to GABA A receptors, we administered α-CZP to cope with the anxiety behavior of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled study evaluating the efficacy of fluoxetine (1mg/kg), one of the selective serotonin reuptake inhibitors, no statistically significant difference in CADESI-03 and PVAS scores was observed between fluoxetine and placebo (Fujimura et al, 2014). Dextromethorphan is an N-methyl-D-aspartate receptor antagonist with some non-specific serotonin reuptake inhibition properties.…”
Section: Alternative Treatment Methods For Pruritus In Cadmentioning
confidence: 99%